Modulating Magnetic Performance in Dyiii Single Ion Magnets with N5o2 Ligands - Aravena-Ponce, D; Aravena-Ponce, D (John Wiley and Sons Ltd, 2024)
[Dy (LMe)(H2O)]CF3SO3·0.25H2O (1·0.25H2O), where H2LMe is the reported ligand 2,2′-(((pyridine-2,6-diylbis (methylene))bis((pyridin-2-ylmethyl)azanediyl))bis (methylene))bis(4-methylphenol), shows the DyIII ion in an N5O3 environment, with triangular dodecahedral geometry (D2d symmetry). 1·0.25H2O is a single ion magnet (SIM) with an energy barrier for spin reversal of 510 K, and open hysteresis loops up to 8 K. The magnetostructural comparison of 1·0.25H2O with some closely related complexes and with other eight-coordinated SIMs with high energy barriers (> 300 K) allows to draw some conclusions to enhance the magnetic performance in these nanomagnets with non-purely axial geometries. Ab initio calculations complement and support the experimental results. © 2024 The Author(s). Applied Organometallic Chemistry published by John Wiley & Sons Ltd.